Unpacking the drivers of service performance: How workload, compensation, and competence influence outcomes through employee satisfaction - Farida, Ida; Soma, AM; Mulyanti, Rita Yuni (Universitas Negeri Surabaya, 2024)
Hospitals must provide exemplary care to patients, with improvements in service standards closely linked to enhanced work quality by medical staff. Effective human resources are essential to healthcare initiatives, especially in the context of services offered to participants of Indonesia's National Health Insurance (BPJS Kesehatan). Despite the government’s commitment to ensuring equal treatment for all patients, discrepancies in the care provided to BPJS and non-BPJS patients persist. Moreover, the high volume of BPJS patients has intensified the workload for healthcare workers, contributing to potential fatigue and burnout. This study, using a quantitative approach and Partial Least Squares (PLS) analysis, investigates how workload, compensation, and competence influence service performance at Harapan Jayakarta Hospital in Jakarta, with employee satisfaction serving as a mediating variable. The findings reveal that both workload and compensation significantly impact service performance. Additionally, compensation and competence are key factors in the mediation of employee satisfaction, while all three variables—workload, compensation, and competence—collectively affect service performance at the hospital. These results underscore the importance of addressing workload and compensation issues to enhance service quality and overall employee well-being in healthcare settings.